The psychological impact of COVID-19 in the general population: A review and reflection in Portuguese Speaking Countries - Sebastião, Rita (2022)
Despite being a global condition, the COVID-19 pandemic, has differential impacts, expressed in different number of cases, deaths, information, political and cultural issues. We review and summarized the literature related to the pandemic of COVID-19 in Portuguese speaking countries. The goal of our review was: 1) summarize the research that reported the prevalence of symptoms of anxiety, depression, post-traumatic disorder, and other indicators of psychological impact in the general population from Portuguese speaking countries, in specific Portugal and Brazil; 2) focus on the COVID-19 related experiences that can be associated with psychological issues; 3) reflect on risk and protective factors that may be associated with psychological distress; and 4) present some reflections about psychological processes that can explain the association between the pandemic and mental health.